Exogenous Plant gma-miR-159a, Identified by miRNA Library Functional Screening, Ameliorated Hepatic Stellate Cell Activation and Inflammation via Inhibiting GSK-3β-Mediated Pathways - Yu WY; Cai W; Ying HZ; Zhang WY; Zhang HH; Yu CH (Dove Medical Press, 2021)
Wen-Ying Yu,1,* Wei Cai,2,* Hua-Zhong Ying,1 Wen-You Zhang,1 Huan-Huan Zhang,1 Chen-Huan Yu1,3,4 1Zhejiang Key Laboratory of Experimental Animal and Safety Evaluation, Zhejiang Academy of Medical Sciences (Hangzhou Medical College), Hangzhou, People’s Republic of China; 2Department of Traditional Chinese Medicine, Zhejiang Pharmaceutical College, Ningbo, People’s Republic of China; 3Institute of Cancer and Basic Medicine, Chinese Academy of Sciences, Hangzhou, People’s Republic of China; 4Cancer Hospital of the University of Chinese Academy of Sciences (Zhejiang Cancer Hospital), Hangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chen-Huan YuInstitute of Cancer and Basic Medicine, Chinese Academy of Sciences, Dongfang Street 150, Hangzhou, Zhejiang, 310018, People’s Republic of ChinaEmail yuchenhuan2002@163.comPurpose: Plant-derived exogenous microRNAs (miRNAs) regulate human physiological functions by blocking the translation of target mRNAs. Although several computational approaches have been developed to elucidate the interactions of cross-species miRNAs and their targets in mammals, the number of verified plant miRNAs is still limited, and the biological roles of most exogenous plant miRNAs remain unknown.Methods: A miRNA mimic library-based phenotypic screening, which contained 8394 plant mature miRNAs published in the official database miRbase, was performed to identify more novel bioactive plant miRNAs for the prevention of hepatic fibrosis. Inhibition of candidates for the activation of hepatic stellate cells (HSCs) and the underlying mechanisms were evaluated in TGF-β 1- and PDGF-exposed HSC models. The protective effects of the candidates against CCl4-induced liver fibrosis were evaluated in a mouse model.Results: Among the 8394 plant mature miRNAs reported in the official database miRBase, five candidates were found to effectively inhibit the differentiation of HSCs. gma-miR-159a (miR159a) exerted the strongest inhibitory activities on both TGF-β 1- and PDGF-induced HSC activation and proliferation by inhibiting the GSK-3β-mediated NF-κB and TGF-β 1 pathways. Moreover, miR159a was mainly accumulated in the liver after intravenous injection, and it reduced CCl4-induced hepatic fibrosis and inflammation in mice.Conclusion: Results indicated that miR159a has the therapeutic potential for preventing hepatic fibrosis. This study provides a novel strategy for achieving natural nucleic acid drugs.Keywords: cross-kingdom regulation, miRNA library, GSK-3β, apoptosis, hepatic fibrosis, inflammation